1982
DOI: 10.1016/s0022-5347(17)53273-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Vena Caval Extension of Renal Cell Carcinoma

Abstract: Vena caval extension of renal cell carcinoma occurs in 4 to 10 per cent of the patients and usually is considered a poor prognostic sign. To ascertain the true effect of vena caval extension on survival a retrospective analysis was done of 27 patients who had undergone radical nephrectomy and removal of vena caval thrombus between 1970 and 1980. An additional 46 cases were collected from series in the literature and composite statistics were compiled. Extension to the vena cava alone had a limited impact on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
6

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(42 citation statements)
references
References 14 publications
4
30
0
6
Order By: Relevance
“…Patient 7 was a high-risk patient with a history of chronic obstructive pulmonary disease and stroke, but patient 3 had no previous medical history. Peri-operative mortality rates of up to 40 % have been reported (8,22,23), but again, as the number of patients in these reports is small the statistics may represent stochastic variation and extensive conclusions should not be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Patient 7 was a high-risk patient with a history of chronic obstructive pulmonary disease and stroke, but patient 3 had no previous medical history. Peri-operative mortality rates of up to 40 % have been reported (8,22,23), but again, as the number of patients in these reports is small the statistics may represent stochastic variation and extensive conclusions should not be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in this group of patients, prognosis is mainly affected by the simultaneous occurrence of local tumor invasion, lymph node involvement and distant metastases [11, 16, 25]. Most authors have reported the 5-year survival rate to be between 47 and 68% for patients with vena caval invasion without lymphatic or hematogenous metastases treated with radical nephrectomy and complete thrombus removal [11, 12, 13, 14, 15, 16, 17]. …”
Section: Discussionmentioning
confidence: 99%
“…Radical surgery, aimed at obtaining the complete removal of the cancer, plays a positive role in patients with RCC extending into the renal vein or vena cava without lymph node involvement or distant metastases [11, 12, 13, 14, 15, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…How ever, in these early studies all patients were included in analysis irrespective of local tumor extension and of lymph node or distant metastasis. The advent of TNM tumor staging has allowed stratification of risk factors and more precise prognostic appraisal, and more recent 1 Paper held on the occasion of Annual Meeting of the Swiss Uro logical Society in 1989. reports reflect an improved prognosis for patients with inferior vena caval involvement [6][7][8], Indeed, Skiner et al [9] drew attention to the fact that the prognosis for such patients does not depend on the thrombus, but pro vided operation was radical with removal of thrombus, on the local extent and on the degree and nature of met astatic spread. Thus, if the kidney tumor and inferior vena caval tumor thrombus can be completely removed, patients with an intracapsular nonmetastatic renal cell carcinoma have better 5-year actuarial survival (55%) than patients with tumor infiltration into the fat capsule of the kidney without caval thrombus [6,10,11], The extension of the tumor into the inferior vena cava may thus be considered as the sole extrarenal manifestation of kidney cell carcinoma which, provided there is radical clearance of tumor, does not affect prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas tumor thrombus in the renal vein does not constitute a particular operative problem, involvement of the inferior vena cava may give rise to major technical difficulty and operative mortality rises to between 3 [7] and 11 % [6].…”
Section: Introductionmentioning
confidence: 99%